2017
DOI: 10.18632/oncotarget.21236
|View full text |Cite
|
Sign up to set email alerts
|

MSC-derived cytokines repair radiation-induced intra-villi microvascular injury

Abstract: Microvascular injury initiates the pathogenesis of radiation enteropathy. As previously demonstrated, the secretome from mesenchymal stem cells contains various angiogenic cytokines that exhibited therapeutic potential for ischemic lesions. As such, the present study aimed to investigate whether cytokines derived from mesenchymal stem cells can repair endothelial injuries from irradiated intestine. Here, serum-free medium was conditioned by human adipose-derived mesenchymal stem cells, and we found that there … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 29 publications
0
20
0
Order By: Relevance
“…In contrast, BM‐MSCs secreted only two (IL‐8 and RANTES) cytokines at higher amounts at P3 compared to P1, and secretion of six cytokines and growth factors (fractalkine, PGDF‐BB, IL‐2, IL‐6, IL‐8, and RANTES) was significantly increased at P5 compared to P1. Multiple studies indicate that the biologic functions mediated by MSCs are dependent on cytokine release by the MSC . Since the cytokine secretion profiles of both AD‐MSC and BM‐MSC seem to be passage dependent, it stands to reason that MSC passage number would also influence their biological potency.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, BM‐MSCs secreted only two (IL‐8 and RANTES) cytokines at higher amounts at P3 compared to P1, and secretion of six cytokines and growth factors (fractalkine, PGDF‐BB, IL‐2, IL‐6, IL‐8, and RANTES) was significantly increased at P5 compared to P1. Multiple studies indicate that the biologic functions mediated by MSCs are dependent on cytokine release by the MSC . Since the cytokine secretion profiles of both AD‐MSC and BM‐MSC seem to be passage dependent, it stands to reason that MSC passage number would also influence their biological potency.…”
Section: Resultsmentioning
confidence: 99%
“…Multiple studies indicate that the biologic functions mediated by MSCs are dependent on cytokine release by the MSC. [14][15][16] Since the cytokine secretion profiles of both AD-MSC and BM-MSC seem to be passage dependent, it stands to reason that MSC passage number would also influence their biological potency. When we compared overall cytokine and growth factor secretion by AD-MSCs with BM-MSCs at P3, we found that AD-MSCs significantly secreted a higher number of cytokines and growth factors at greater concentrations.…”
Section: Cytokine Secretion Profiles Differ Between Ad-mscs and Bm-mscsmentioning
confidence: 99%
“…Kennelly et al (31) reported that human MSC-derived HGF exerted an antiapoptotic effect in chronic obstructive pulmonary disease. Chang et al (32) determined that several angiogenic cytokines, including HGF, protected endothelial cells against radiation-induced apoptosis and accelerated the recovery of irradiated mice. To determine whether HGF enhanced autophagy, the present study investigated HK-2 cells treated with rhHGF and the results suggested that rhHGF increased HK-2 cell autophagy.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it is unknown whether longer culture times result in more robust effects. A study by Chang, used different time points, including 6, 12, 24, 48, and 72 hours for placental cell-derived CM [47] and 1, 3, 5, 7, 10, and 14 days for placental tissue-derived CM, to achieve optimal effects. The results showed that the optimal time points for placental cell-derived CM were 24 and 48 hours but not 72 hours.…”
Section: Discussionmentioning
confidence: 99%